2020
DOI: 10.3389/fphy.2020.567800
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Monte Carlo Simulations as Clinical and Research Tool in Particle Therapy: A Review

Abstract: The use and interest in Monte Carlo (MC) techniques in the field of medical physics have been rapidly increasing in the past years. This is the case especially in particle therapy, where accurate simulations of different physics processes in complex patient geometries are crucial for a successful patient treatment and for many related research and development activities. Thanks to the detailed implementation of physics processes in any type of material, to the capability of tracking particles in 3D, and to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 233 publications
(256 reference statements)
0
25
0
Order By: Relevance
“…Another possibility is the usage of fast MC simulation codes, which are being more and more frequently used in clinical practice. 52…”
Section: Free Parametersmentioning
confidence: 99%
“…Another possibility is the usage of fast MC simulation codes, which are being more and more frequently used in clinical practice. 52…”
Section: Free Parametersmentioning
confidence: 99%
“…In this work, we have analyzed the previously published comprehensive database of PARTRAC simulations on DNA damage induced by light ions [20,21]. Model cell nuclei were irradiated by 1 H, 4 He, 7 Li, 9 Be, 11 B, 12 C, 14 N, 16 O or 20 DSBs, DSB clusters and DSB sites were scored. From absolute numbers of the lesions and the deposited dose, damage yields per Gy per Gbp were calculated.…”
Section: Partrac Track-structure Simulationsmentioning
confidence: 99%
“…Radiation transport codes are a key tool for many research and practical applications dealing with radiation-matter interactions. Many codes exist, including FLUKA, Geant4, MCNP, PHITS or TOPAS [1][2][3][4][5]; recent reviews focused on radiotherapy applications can be found in [6,7]. In most cases a common issue has to be faced: The radiation field and the resulting dose distribution have to be captured at a rather large spatial scale, e.g., in a human body, in a high-energy physics detector, or in a shielding layer in a space habitat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This quantity, needed to calculate biological dose and to predict treatment outcomes, demonstrates a complex dependency on several physical and biological parameters, among which the spectrum of nuclear fragments produced in interactions of the particle beam with the patient tissue [2][3][4]. To simulate the biological effect of these fragments and take it into account in particle therapy treatment planning, it is important to accurately model their production [5,6]. Differential cross section measurements for nuclear fragment production in thin targets are the most valuable for this purpose.…”
Section: Introductionmentioning
confidence: 99%